The impact of autoimmune diseases on delirium risk in critically ill patients: a propensity score matching multicenter analysis - Huang, Shi-Tao; Yu, Kai-Hua; Yuan, Jing-Wen; Sun, Yi-Bo; Huang, Zhong-Ya; Liu, Li-Ping (Frontiers in Medicine, 2025)
BackgroundDelirium, an acute neuropsychiatric syndrome characterized by disturbances in attention, cognition, and consciousness, is a prevalent manifestation of acute brain dysfunction among intensive care unit (ICU) patients. It is considered within the mental health framework as a transient but serious disorder of cognition and behavior. Autoimmune diseases (AID), characterized by systemic inflammation and immune dysregulation, may impact central nervous system function. Currently, their role in delirium pathogenesis among ICU patients remains unclear. This study aimed to evaluate the association between autoimmune diseases and delirium incidence in ICU patients.MethodsUsing the eICU Collaborative Research Database, we identified patients with first ICU admissions and documented assessment of delirium. Patients were categorized into AID and non-AID groups. Propensity score matching (PSM) and inverse probability weighting (IPTW) were applied to balance key baseline covariates, including demographics, comorbidities, clinical interventions, and severity scores. The primary outcome was delirium occurrence. The association between AID and the occurrence of ICU delirium was evaluated using Cox proportional hazards and competing risk models, with sensitivity and subgroup analyses to assess the stability of the results.ResultsAmong 8,978 patients (1,007 with AID; 7,971 without), delirium occurred in 29.7% of the cohort. In both crude and matched cohorts, AID was significantly associated with increased delirium risk in univariate and multivariable Cox analyses (p < 0.001). Fine and Gray models confirmed a higher delirium incidence in the AID group after accounting for competing risks of in-ICU mortality (p < 0.001). The KM curves show no significant difference in-ICU mortality rate between the two groups.ConclusionThis study found a significant correlation between AID and the incidence of delirium in ICU, emphasizing the need for heightened delirium surveillance and early intervention in AID patients.